Development of personal finance mobile application with Optical Character Recognition (OCR) technology for automated receipt management and expense tracking - Tan, Su Hua (2023)
Managing receipts has always been considered as a hassle and troublesome task, especially when dealing with a large number of receipts. However, keeping track of receipts is crucial for various purposes, including tax audits, as evidence of purchases, and facilitating returns or refunds. This project aims to simplify the process of managing finances and receipts by integrating Optical Character Recognition (OCR) technology into a financial planning application. OCR is the short form for Optical Character Recognition. It is a technology that was powered by Machine Learning algorithms like Convolutional Neural Networks (CNN) whereby it allows extraction of text from images or documents in a blink of eye. With the implementation of OCR technology, information from receipts, such as merchant names, dates, and amounts, it can be effortlessly retrieved, making receipt management significantly more accessible and time efficient. Then, the extracted data is displayed to the user and concurrently stored in cloud storage for future reference, such as tax audits and proof of purchase or refunds. Besides receipt management, the application offers an array of functions to assist individuals in effectively planning and managing their finances and have better vision on their financial status in real time. Users can track their daily financial transactions, establish budget plans, and more. These functions encourage financial responsibility, a critical factor in achieving one's financial goals. Furthermore, user inputs are transformed into insightful graphical representations such as bar chart and pie chart, providing users with a comprehensive view of their financial status. Moreover, users can also generate personalized financial reports according to their preferences. For instance, producing an expense report for a specific period within few steps and these reports can be serve as a vital decision-making tool for users in managing their finances. In summary, this project addresses the challenges of receipt management and other issues by leveraging OCR technology within a comprehensive financial planning application. It aims to empower users to efficiently handle their finances, fostering better financial habits and enabling more informed financial decisions.